Market Integration of Horticultural Commodity Between Angsoduo and Talang Banjar in Jambi City - Kemala, Nida; Asmaida, Asmaida; Falah, Agil Ahmad (Universitas Batangahari Jambi, 2024)
The horticulture commodities (chilies and shallots) acts as a food ingredient. Market efficiency needs to be considered in order to achieve economic stability, so it needs to be studied their market integration (between Angsoduo and Talang Banjar Market). This research aims to: analyse commodity prices phenomena and market integration. Data were analysed descriptively and inferentially by using the Coefficient of Variance (CV), t test and the Market Connection Index (IMC). The results showed that there was no difference in the variance or price of chilies on the different market. IMC value for red chilies was less than one (-0,165< 1), which means there was integration between Talang Banjar and Angsoduo Market. There was a significant difference between shallot price in both market. As well as there was also a significant difference on variance of shallot prices between the two market (Talang Banjar (1.0875) and Angsoduo (0.0426)) but there is no market integration on shallot (IMC (7.89) > 1). Keywords: shallots, chilies, price, horticulture, stability